2022
DOI: 10.4012/dmj.2021-247
|View full text |Cite
|
Sign up to set email alerts
|

Collagen stabilization by natural cross-linkers: A qualitative and quantitative FTIR study on ultra-thin dentin collagen model

Abstract: Due to its low tolerance to external factors such as enzymes, dentin collagen often requires stabilization, which can be achieved through cross-linking. In this study, qualitative and quantitative Fourier transform infrared (FTIR) analyses were used to assess dentin collagen stabilization effects of three structurally-different flavonoids -A-type linkage proanthocyanidins (A-PA), B-type linkage proanthocyanidins (B-PA), and epigallocatechin gallate (EGCG), all from natural extracts. Particularly, transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Furthermore, an intriguing observation was the shift of the amide III vibration of the membranes (initially at ~1240 cm −1 ) to a peak at ~1230 cm −1 because of the in-plane bending of C–N and N–H. 37 Furthermore, XPS imaging of collagen membranes after 7 and 14 d of incubation showed the presence of cerium, and the ratio of Ce (IV) to Ce (III) was 54.12%: 45.88% (7 d) and 74.7%: 25.3% (14 d) respectively.
Figure 2 TEM, HRTEM, FTIR and XPS images of collagen membranes treated with BMS.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an intriguing observation was the shift of the amide III vibration of the membranes (initially at ~1240 cm −1 ) to a peak at ~1230 cm −1 because of the in-plane bending of C–N and N–H. 37 Furthermore, XPS imaging of collagen membranes after 7 and 14 d of incubation showed the presence of cerium, and the ratio of Ce (IV) to Ce (III) was 54.12%: 45.88% (7 d) and 74.7%: 25.3% (14 d) respectively.
Figure 2 TEM, HRTEM, FTIR and XPS images of collagen membranes treated with BMS.
…”
Section: Resultsmentioning
confidence: 99%
“…The peak at ~1545 cm −1 of amide II was shifted to ~1490 cm −1 which was associated with C=O stretching, and the peak at ~1640 cm −1 of amide I was shifted to ~1630 cm −1 which was associated with N–H bending and C–N stretching. 37 These were caused by the incorporation of cerium oxide in the mineralizing dentin. XPS analysis of dentin surface ( Figure 3h ) mineralized for 7 and 14 d showed that the ratio of tetravalent to trivalent cerium was 30.4%:69.6% for 7-day mineralized samples and 62.28%:37.72% for 14-day samples.…”
Section: Resultsmentioning
confidence: 99%
“…Proanthocyanidins (PA), which make up a significant fraction of the extract we used, have been shown to induce effects both to the secondary and tertiary structure of collagen, and a significant role for hydrogen bonding in the stabilization of collagen by PA has been suggested [48][49][50]. Besides hydrogen bonding, true covalent interactions have been detected by infrared spectroscopy between PA and collagen [51,52]. In particular, they occur through autooxidation of catechol moieties to ortho-quinone groups, available for Schiff base formation with free amine groups on proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the highest values recorded in groups using the total-etch mode, disregarding the dentine pre-treatment agents used. On the other hand, stable bonds can only be achieved if the adhesive infiltrates uniformly the etched dentine in order to prevent the different degrees of incomplete infiltration (20) that, if happens, a trapped demineralized zone at the bottom of the hybrid layer (HL) will occur (21) .…”
Section: Discussionmentioning
confidence: 99%